Remote practicals in the time of coronavirus, a multidisciplinary approach. Issue 2 (April 2022) - Bangert, K; Bates, J; Beck, SBM; Bishop, ZK; Di Benedetti, M; Fullwood, J; Funnell, AC; Garrard, A; Hayes, SA; Howard, T; Johnson, C; Jones, MR; et al.
Due to the COVID-19 pandemic, universities across the world have curtailed face to face teaching. Associated with this is the halt to the delivery of the practical experience required of engineering students. The Multidisciplinary Engineering Education (MEE) team at The University of Sheffield have responded to this problem in an efficient and effective way by recording laboratory experiences and putting videos, quizzes and data online for students to engage with. The focus of this work was on ensuring all Learning Outcomes (LOs) for modules and courses were preserved. Naturally, practical skills cannot be easily provided using this approach, but it is an effective way of getting students to interact with real data, uncertainty and equipment which they cannot access directly. A number of short case studies from across the range of engineering disciplines are provided to inspire and guide other educators in how they can move experiments on line in an efficient and effective manner. No student feedback is available at the time of writing, but anecdotal evidence is that this approach is at least acceptable for students and a way of collecting future feedback is suggested. The effort expended on this approach and the artefacts produced will support student learning after the initial disruption of the lockdown has passed.